Outcomes of whole-body photobiomodulation on pain, quality of life, leisure physical activity, pain catastrophizing, kinesiophobia, and self-efficacy: a prospective randomized triple-blinded clinical trial with 6 months of follow-up - Navarro-Ledesma, Santiago; Carroll, James D.; González-Muñoz, Ana; Burton, Patricia (Frontiers in Neuroscience, 2024)
The management of fibromyalgia (FM) symptoms on a global scale remains a complex endeavor. This study endeavors to assess the impact of whole-body photobiomodulation (PBM) compared to placebo PBM on pain, functionality, and psychological symptoms in individuals afflicted with fibromyalgia.The primary objectives of this research were to conduct a comparative analysis of the effects of whole-body photobiomodulation (PBM) and placebo PBM on pain, functionality, and psychological symptoms in patients suffering from fibromyalgia (FM).Methods: A total of 42 subjects were recruited from a private care practice for participation in this triple-blinded, placebo-controlled, randomized clinical trial. Participants underwent 12 treatment sessions, and assessments were conducted at various intervals, including baseline (T0), midway through the 12-session treatment (T1), at the completion of the 12 sessions (T2), and follow-ups at 2 weeks (T3), 3 months (T4), and 6 months (T5).Results: Statistical analysis revealed significant reductions in pain at T2, T3, and T5.Additionally, quality of life exhibited marked improvements after sessions at T1, T2, T3, T4, and T5. Leisure activity also demonstrated statistically significant improvements at T2, T3, T4, and T5. Furthermore, kinesiophobia showed significant differences between groups immediately after treatment at T2, T3, T4, and T5. Self-efficacy, when compared between groups, demonstrated significant differences at T3, T4, and T5 (two weeks after treatment).Lastly, pain catastrophizing exhibited significant differences only at T5.The findings of this study indicate that whole-body PBM treatment for four weeks resulted in significant pain reduction and improved quality of life in individuals suffering from FM. Furthermore, kinesiophobia and self-efficacy demonstrated improvements in both short-term and long-term assessments, while pain catastrophizing showed improvement at the 6-month follow-up. Consequently, whole-body PBM emerges as a promising multifactorial treatment option for FM patients, though further studies are required to validate and strengthen these results.